Pengaruh Metode Pembelajaran Inquiry Training terhadap Hasil Belajar Siswa - Ova Grace; Deden Ibnu Aqil (INTELEKTIUM, 2020)
The purpose of this study was to determine the effect of Inquiry Training Learning Methods on the Learning Outcomes of Business Economics in Class X SMK Pertiwi Jakarta. The method used in this study is an experiment which is divided into experimental class and control class. Samples taken came from the population of class X Accounting and Marketing X SMK Pertiwi Jakarta as many as 60 students consisting of 30 students in the experimental class and 30 students in the control class. The sampling technique consisted of 2 stages: (1) purposive sampling technique (2) simple random sampling technique. The technique of collecting data on variable student business economics learning outcomes was carried out by giving multiple choice questions for the variable student business economics learning outcomes. In the hypothesis test, the t-test is used which results in tcount > ttable, so the conclusion is that there is an influence of the Inquiry Training learning method on student learning outcomes in class X business economics subjects so that the Inquiry Training learning method can be used as an alternative for teachers in carrying out learning to create a learning atmosphere effective and students become more active.